Feasibility of wave energy harvesting in the Ligurian Sea (Proceedings of the European Wave and Tidal Energy Conference, 2023)
A series of short and mid-term guidelines have been established due to the pursuit to offer clean energy and reduce the environmental impact in the Mediterranean and European environment. Currently, the scientific community and the industrial sector promote to find new technologies and means to achieve these regulations. Efforts to provide sustainable ways to supply electricity in Italy have led to the exploration of marine renewable energies (MRE) in the Mediterranean Sea. In particular, in the Ligurian Sea, where the wave climate can provide one of the higher energy sources, represents an optimal opportunity for supplying this energy resource to coastal cities. However, the wave conditions are not as significant as those in other marine regions around the world. There are several devices currently developed which can be applicable to the region. Hence, an evaluation from a technical and economic perspective is advised. Additionally we also investigate the scaling and survival considerations for Wave Energy Converters (WECs) when facing extreme storm events. The proposed study offers the evaluation of a sustainable alternative for powering the electricity mix in the Liguria region, through the exploitation of the wave energy resource. Attractive findings emerge after the assessment of eight floating-body wave energy converters.